2021
DOI: 10.1177/02654075211016542
|View full text |Cite
|
Sign up to set email alerts
|

The trajectory and determinants of loneliness during the early months of the COVID-19 pandemic in the United States

Abstract: In March of 2020, state governments in the United States began implementing stay-at-home orders in an attempt to curtail the spread of COVID-19. As a result, most people experienced a decrease in face-to-face interactions as they limited their participation in social gatherings, travel, and in-person work. Although these orders aimed to stop the spread of COVID-19, a potential unintended consequence of these guidelines was an increase in loneliness, which has several negative mental and physical health consequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 56 publications
3
21
1
Order By: Relevance
“…COVID‐19‐related school closures and stay‐at‐home orders may therefore have increased risk of feelings of loneliness in young people (Bu et al, 2020 ; Magson et al, 2021 ). Studies conducted with adults (age range 18–88 years) have shown that COVID‐19 either led to increased feelings of loneliness (for a review, see Buecker & Horstman, 2021 ) or had no effect on feelings of loneliness (Bu et al, 2020 ; Luchetti et al, 2020 ; Ray, 2021 ). According to Buecker and Horstmann ( 2021 ), the evidence about pandemic containment measures being associated with changes in perceived quality or quantity of social relationships, or both, is inconclusive because studies have not examined these processes.…”
Section: Introductionmentioning
confidence: 99%
“…COVID‐19‐related school closures and stay‐at‐home orders may therefore have increased risk of feelings of loneliness in young people (Bu et al, 2020 ; Magson et al, 2021 ). Studies conducted with adults (age range 18–88 years) have shown that COVID‐19 either led to increased feelings of loneliness (for a review, see Buecker & Horstman, 2021 ) or had no effect on feelings of loneliness (Bu et al, 2020 ; Luchetti et al, 2020 ; Ray, 2021 ). According to Buecker and Horstmann ( 2021 ), the evidence about pandemic containment measures being associated with changes in perceived quality or quantity of social relationships, or both, is inconclusive because studies have not examined these processes.…”
Section: Introductionmentioning
confidence: 99%
“…During the pandemic, public health officials cautioned against extra-familial social interactions, even warning against extended family gatherings, and public communal spaces such as bars and churches, which may have held special importance for non-married adults as primary spots for socializing, were shut down around the US ( Thomeer et al 2020 ). The social conditions around the pandemic increased social isolation and loneliness within society ( Ray 2021 ; van Mulukom et al 2020 ), perhaps especially for the non-married, and consequently may have increased health disparities by relationship status.…”
Section: Introductionmentioning
confidence: 99%
“…A similar search using keywords 'teacher loneliness' returns a few dedicated results (predominantly associated with pandemic lockdowns) (Jandrić et al 2020(Jandrić et al , 2021. 'Researcher loneliness' seems to offer the most relevant results (see Gannon-Leary et al 2011), yet most of these results are (again) associated with pandemic lockdowns (Ray 2021) and/or focused on early career researchers such as PhD students (Cantor 2019). Looking at (more) senior academic levels, scholarly research on loneliness is few and far in between.…”
Section: Alone-time and Loneliness In Literaturementioning
confidence: 99%